Nurses' Knowledge and Practice Regarding Gynecological Laparoscopy in Maternity Teaching Hospital in Mosul City - Rana Mohammed Jasim AL-Taee; Salwa Hazim Al -Mukhtar (College of Nursing,University of Mosul, 2015)
Background and aim: Over the past decade, laparoscopy has become the standard surgical approach for a majority of gynecologic procedures, such as ectopic pregnancy management, fallopian tube and ovarian operations, management of cysts, staging of gynecologic cancers, and laparoscopically assisted vaginal hysterectomy. The study aim to assess nurses level of knowledge and practices regarding gynecological laparoscopy, To determine the knowledge defect during gynecological laparoscopy, and to determine the difference between demographic characteristics such as (age, level of education, and training courses) with their knowledge and practices. Materials and Method: The researcher adopted a quantitative design where structured closed-ended questions were formulated for both questionnaires. A questionnaire was administered to the Ward and Theatre Nurses using the convenience sampling technique. The study was conducted in two hospitals ( Al Batool and AL-Khansaa Teaching Hospitals ) located in Mosul city. Statistical Package for Social Sciences (SPSS) version 15 for Windows was used by the Statistician to analyze the data. Results: The findings shows the demographic characteristics of the study sample. The table shows that most of the study sample are from AL-Khansaa Hospital (50.9%). According to the age, the highest percentage was in the age group (18-27 years) (43.6%), and the lowest group are of age (more than 47 years) (8%). According to level of education the highest percentage is of High school (56.4%) (62), and the lowest is (12.7%) (14). In the relation to their Experience, the highest percentage is (74.5%) for the group of (1-10 years), and the lowest percentage is (6.4%) for the group of (more than 30 years). Conclusions: The nurses' had good knowledge about the specific laparoscopic . Recommendation: Ward and theatre nurses should be learn about informed consent taking and the legal implications if not taken correctly and the emphasis on their role and responsibilities during consent taking. This could be done during in-service education. Keywords: Nurses' Knowledge, Practice, Gynecological Laparoscopy.